Use of Pedagogical Technologies Tools in the Professional Training of Future Officers in Higher Military Educational Institutions - Seliuk, Volodymyr (Pedagogical Discourse, 2023)
The relevance of using pedagogical technologies in the educational environment of higher education institutions is proved in the article. The importance of using the latest teaching technologies on the way to enhance the level of training of specialists in various fields is justified. Attention is focused on the fact that the use of pedagogical technologies has a qualitative impact on the training of specialists in the military sector. According to the purpose of the article (consideration of pedagogical technologies used in the system of higher military education of Ukraine for their potential to improve the quality of training of future officers) and the defined tasks, the essence of the concept of «pedagogical technologies» is clarified in a retrospective analysis of research, approaches to the classification of pedagogical technologies are analyzed. It is proved that the term «pedagogical technologies» is widely used in all aspects of the educational process (management, organizational), however, its lexical expansion is interpreted differently. The article defines and describes the levels of functioning of the studied phenomenon (general pedagogical, subject, modular), and highlights key methodological requirements and criteria of technological feasibility. The research of scientists on understanding the essence of the concept of «learning technologies» is analyzed. The role of pedagogical technologies in the functioning of the system of higher military education is studied. Special attention is given to the importance of pedagogical technologies in the educational, instructional, and managerial aspects of Higher Military Educational Establishments. Through the analysis of research on the use of «pedagogical technologies», the differences between the scientific substantiation of the concept’s content and its impact on the formation of professional competence of specialists are identified. Based on the analysis of the research, it is found that the most effective thing in the training of future military personnel are innovative technologies (simulation modeling technologies; project-based technologies; training technologies; workshops; coaching), which enhance the possibility of further improving practical skills. In addition, it is determined that project technologies have high potential in the system of cadet training in Higher Military Educational Establishments. The possibilities of using information and communication technologies in the educational process of Higher Military Educational Establishments are described, the effectiveness in distance learning is proven. The importance of applying simulation technologies (military simulators, virtual training grounds, computer simulations) in the process of training officers is justified, which, according to practitioners, help cadets acquire practical skills in conditions close to real-life ones, ensuring the formation of such personal qualities as stress resistance, psychological readiness. The feasibility of using role-playing games, situational tasks, group discussions, debates is described, it is determined that such forms of work contribute to the formation of leadership qualities in future military personnel, the ability to make the right decisions in extreme situations and develop communication skills. The conclusion states that the importance of using pedagogical technologies in the process of training future officers of the Armed Forces of Ukraine is undeniable, since the level of professional competence of graduates of Higher Military Educational Establishments depends on the preservation of the territorial integrity and sovereignty of our country, its defense capability, and national security in general. Prospects for further research are outlined, which are based on the development of organizational and pedagogical conditions and the construction of a structural and functional model for forming the corporate culture of the Future Officers of the Armed Forces of Ukraine by means of pedagogical technologies.